La Metamorfosis: una exploración al narcotráfico, crimen organizado e insurgencia en Chile - Lagos Flores, Roberto (2023)
This article analyzes the main factors of change that have occurred in Chile in terms of drug trafficking, organized crime, and insurgent action in certain parts of the country. This analysis is based, first, on the hypothesis that the country has ceased to be just a transit route for drugs and has become a place of destination (receiver), based on a set of facts that place it in a new category within the regional drug trafficking map, despite the fact that its role as a transit country (transmitter) continues; second, its role is argued in an incipient network of transnational organized crime networks connected with local structures that are in full development, dedicated to crimes of a certain magnitude in the narco world; third, the presence of illicit associations that still operate in limited areas of the national territory and that claim a subversive and criminal fight is described.